2017
DOI: 10.1182/bloodadvances.2016002691
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation prevents right ventricle disease in the caveolin-1–deficient mouse model of pulmonary hypertension

Abstract: • Caveolin-1 deficiency in hematopoietic stem cells induces right heart disease.• Healthy BM protects the right heart from maladaptation.Accumulating evidence shows a causative role for the bone marrow (BM) in the genesis and progression of pulmonary hypertension (PH). Engraftment of BM hematopoietic stem cells from PH patients to mice reproduces the cardiopulmonary pathology of PH. However, it is unknown whether healthy BM can prevent the development of right heart disease.Caveolin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The inflammatory phenotype that we observed, while mild, is particularly interesting in the context of a recent publication in which reciprocal bone marrow transplants between wild-type and Cav1 −/− animals suggested that the pulmonary hypertensive phenotype of Cav1 −/− was being driven by circulating cells (38). We are not the first to see an association between macrophages and Cav1.…”
Section: Discussionmentioning
confidence: 46%
“…The inflammatory phenotype that we observed, while mild, is particularly interesting in the context of a recent publication in which reciprocal bone marrow transplants between wild-type and Cav1 −/− animals suggested that the pulmonary hypertensive phenotype of Cav1 −/− was being driven by circulating cells (38). We are not the first to see an association between macrophages and Cav1.…”
Section: Discussionmentioning
confidence: 46%
“… 13 , 35 In contrast, substantial right ventricle fibrosis is observed in models of decompensated right ventricle failure including Sugen/hypoxia, pulmonary artery banding combined with Cu 2+ -depleted diet or high dose monocrotaline treatment, 13 , 35 , 63 and caveolin-1-deficient mice. 64 67 Collagen synthesis kinetics in rabbits with increased right ventricle afterload caused by pulmonary artery banding showed a rapid increase in right ventricle collagen synthesis followed by degradation, 68 supporting the notion that controlled fibrosis may be part of a reparative process in compensated right ventricle hypertrophic response. 69 Growth factors and cytokines involved in cardiac fibrosis have been elegantly reviewed in a previous report.…”
Section: Right Ventricular Fibrosismentioning
confidence: 77%
“… 74 In line with these findings, another report showed that right ventricle fibrosis in caveolin-1-deficient mice is prevented by transplantation of WT bone marrow independent of pulmonary vascular disease. 64 Whether caveolin-1 affects bone marrow hematopoietic stem cell-derived fibroblast progenitors needs to be further investigated. Fibrocytes, a subset of circulating hematopoietic cells with established role remodeling of the pulmonary artery wall in animal models of PAH 75, 76 may also be involved in cardiac fibrosis.…”
Section: Right Ventricular Fibrosismentioning
confidence: 99%
“…Since it is known that hypoxia/ischemia is one of the leading causes of heart failure and stroke, studies were performed to assess whether acute hypoxia can cause deleterious cardiac remodeling. C57Bl6 mice were placed in hypoxia chamber for 20 hours [27] and cardiac function was assessed by echocardiography. Acute hypoxia resulted in deleterious cardiac remodeling as observed by increased cardiac lumen post-hypoxia (n=12) [ Fig.…”
Section: Resultsmentioning
confidence: 99%
“…C57/BL6 wild type (WT) mice of either sex 3-6 months of age were subjected to hypoxia (10% O2) [27] or normoxia for 20 hours. The studies were performed in accordance with institutional and national guidelines and regulations, as approved by Cleveland Clinic Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%